Perspectives and Practices of Healthcare Leaders in Supporting Healthcare Worker Well-Being: A Reality Check - Reijmerink IM; van der Laan MJ; Scheele F; Wietasch JKG (Journal of Healthcare Leadership)
Iris M Reijmerink,1 Maarten J van der Laan,1 Fedde Scheele,2,3 J K Götz Wietasch4 1Department of Surgery, University Medical Centre Groningen, Groningen, the Netherlands; 2Amsterdam Academic Medical Center, Research in Education, Amsterdam, the Netherlands; 3Athena Institute for Trans-Disciplinary Research, the Vrije Universiteit Amsterdam, Amsterdam, the Netherlands; 4Department of Anaesthesiology, University Medical Centre Groningen, Groningen, the NetherlandsCorrespondence: Iris M Reijmerink, UMCG, Hanzeplein 1, Groningen, 9713GZ, The Netherlands, Tel +316 38 15 85 58, Email i.m.reijmerink@umcg.nlIntroduction: The well-being of healthcare workers (HCWs) is a critical concern. While healthcare leaders can play a crucial role in influencing employees’ well-being, it remains unclear how leaders are leveraging this influence. This study aims to unravel the current perspectives and practices of healthcare leaders in supporting HCW well-being.Methods: Semi-structured interviews were conducted with healthcare leaders at various levels within a university medical center. The interviews focused on exploring three key topics: factors influencing HCW well-being, data sources utilized for information gathering, and strategies leaders employ to influence HCW well-being. Our study design was grounded in constructionist epistemology and adopted a phenomenological approach. The methodology primarily involved a data driven, inductive thematic analysis to discern patterns and themes from the collected data.Results: Fifteen interviews with healthcare leaders revealed a multitude of factors influencing HCW well-being, categorized into three domains: personal, socioeconomic, and work-related factors. Leaders reported a variety of data sources, including “contact data”, data derived from regular and sporadic interpersonal interactions, and “investigation data”, entailing formal inquiries conducted within the healthcare organization. Interestingly, while leaders acknowledge their potential to positively influence well-being, particularly in work-related aspects, there was a notable trend of deflecting responsibility, often redirecting it towards other leaders or placing it back on the individual employee.Conclusion: Healthcare leaders show a comprehensive understanding of factors affecting employee well-being. However, healthcare leaders have a predominantly reactive approach to managing employees’ well-being. Data collection is often sporadic, lacking consistency, and there is a tendency to redirect responsibility for well-being, revealing a discrepancy between acknowledgement of influence and its actual implementation. We argue that it is essential for leaders at all hierarchical levels to assume responsibility actively and collectively for employee well-being, transitioning to a proactive approach in promoting and safeguarding the well-being of HCWs.Plain Language Summary: Healthcare workers play a key part in the healthcare system, so their well-being is very important. This became especially clear during the COVID-19 pandemic. Healthcare leaders can help improve their employees’ well-being, but it’s not always clear how well they do this, or if they do it at all.In this study, researchers looked at how healthcare leaders notice and affect the well-being of their workers. They talked to leaders at different levels in a hospital, asking what they think affects their workers’ well-being, where they get their information about it, and how they try to improve it.The study showed that leaders know many things that can affect well-being, like personal problems, money issues, and work-related problems. Leaders usually learn about well-being through informal chats or formal reviews in the hospital. However, even though leaders know they can make a difference, they often leave this to others or say it’s up to the workers themselves.The findings of this study suggest that healthcare leaders should be more involved in supporting their employees’ well-being. By doing so, they can help protect health care workers and strengthen the healthcare system.Keywords: healthcare worker well-being, employee well-being, leadership, healthcare leaders